2005
DOI: 10.2169/internalmedicine.44.907
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Fucosidosis Through A Skin Rash

Abstract: Angiokeratoma corporis diffusum (AKCD) is a dermatological hallmark of several inherited lysosomal storage disorders, including Anderson-Fabry disease, -galactosidosis, fucosidosis, aspartylglucosaminuria, galactosialidosis, -mannosidosis, and Kanzaki disease (1-3).A 50-year-old Japanese woman, the product of a consanguineous marriage, was admitted to our hospital for repeated respiratory tract infections and chronic heart failure due to hypertrophic obstructive cardiomyopathy. She had short stature, gargoyle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…19 Recurrent respiratory infections may occur. Patients then develop hypertonia and, later in the course, spasticity, tremor, and mental deterioration, leading to loss of contact with their environment.…”
Section: Clinical Picturementioning
confidence: 99%
See 2 more Smart Citations
“…19 Recurrent respiratory infections may occur. Patients then develop hypertonia and, later in the course, spasticity, tremor, and mental deterioration, leading to loss of contact with their environment.…”
Section: Clinical Picturementioning
confidence: 99%
“…40 Peripheral neuropathy with thenar and hypothenar atrophy has been reported. Tsukadaira et al 19 reported that angiokeratoma corporis diffusum (AKCD) is a feature of a number of lysosomal disorders including Anderson-Fabry disease, β-galactosidosis, fucosidosis, aspartylglucosaminuria, galactosialidosis, β-mannosidosis, and Kanzaki disease, and included an excellent color photo of AKCD. Intrafamilial heterogeneity has been noted.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Eine erhöhte Oligosaccharid-Ausscheidung im Sammelurin eignet sich als Screeningtest. Die Diagnose wird durch eine erniedrigte oder fehlende Aktivität der alpha-Fukosidase gesichert [36,62]. Patienten mit Fukosidose können eine Tortuositas der konjunktivalen Bindehautgefäße mit Aussackungen aufweisen, eine entsprechende Schlängelung der Netzhautgefäße wie bei Morbus Fabry wurde bisher nicht beobachtet.…”
Section: Fukosidoseunclassified
“…Type 1 has been reported as having a severe infantile presentation (neurological functions being highly affected before 1 year of age) while type 2 has progressive features, increasing patient's life expectancy to 25‐35 years of age . Fucosidosis patients’ skin abnormalities include angiokeratoma corporis diffusum (which is also present in other metabolic diseases), widespread telangiectasia, skin thickness, hyperhidrosis and hypohidrosis, acrocyanosis and distal transverse nail bands . It has been described that >50% of fucosidosis patients have angiokeratoma which tends to spread over the body of older patients, such lesions, located in the papillary dermis, are characterised by proliferative ectatic blood vessels limited by a flattened endothelium containing erythrocytes .…”
Section: Introductionmentioning
confidence: 99%